Design, Implementation, and Usability Evaluation of the Iranian Primary Vitiligo Patient Registry. - Arabkermani, Zahra; Sharifian, Roxana; Aryanian, Zeinab; Bastani, Peivand; Esmaeli, Nafiseh; Bashiri, Azadeh; Sheikhtaheri, Abbas (Journal of the Dermatology Nurses' Association)
INTRODUCTION: Vitiligo is an acquired pigmentary disorder, which is usually progressive and irreversible if left untreated. Structured databases such as registries are required to continuously collect standard data about patients with the same disease. OBJECTIVES: This study aimed to design and implement a vitiligo registry and evaluate its usability in Iran. METHODOLOGY: This research was conducted in four stages: determining the minimum data set required for the registry, creating a conceptual model using unified modeling language diagrams and Sparx Enterprise Architect software, implementing the registry in the PhpStorm programming environment, and evaluating the software usability based on the responses of 17 end users to a questionnaire. RESULTS: The required data items, consisting of 127 items in eight categories, were approved by the experts and used to design the vitiligo registry. Then, the software was designed and implemented. In the assessment stage, the software received a 89.5% approval rate from its users. CONCLUSION: Developing a vitiligo registry with high usability as well as making decisions based on the registry data can improve understanding of the disease and facilitate research in this field. As a result, high-quality services could be provided to patients nationwide.